Penyelesaian Sengketa Lahan Hutan Melalui Proses Mediasi Di Kabupaten Siak - Riska Fitriani (Fakultas Hukum Universitas Riau, 2012)
Disputes out of court settlement is also called alternative dispute Resolution (ADR) One dispute is between the investor and the community in the District of Kerinci Siak Kanan. Settlement is done by negotiation efforts, that is the process of negotiating or bargaining a concession, on the problems that arise in the community.